Effect of Calcination Temperature on Surface Morphology and Photocatalytic Activity in TiO2 Thin Film Prepared by Spin Coating Technique - Krishna Krishna Mothi; G. Soumya; S. Sugunan (Bulletin of Chemical Reaction Engineering & Catalysis, 2014)
TiO2 thin films were deposited on glass substrate using Sol-Gel derived precursor by Spin Coating technique at different calcination temperatures. Structural identity of the prepared films was con- firmed by powder X-ray diffraction measurements. Morphology of the films was monitored using Atomic force microscopy and it was observed that calcination temperature of 400 °C favored TiO2 nano- fibers. Photocatalytic activity of the films was checked by observing the degradation of herbicide Atrazine in UV region and the percentage of degradation was analyzed by HPLC method. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)